Diagnóstico e Prognóstico da vila Nossa Senhora do Trabalho, Santa Maria-RS - Becker, Elsbeth Léia Spode; Scheneiders, Agostinho; Bitencourt, Luciane Rodrigues de; Zibordi, Antonio Francisco Guerreiro (Geografia Ensino & Pesquisa, 2016)
Diagnóstico e Prognóstico da vila Nossa Senhora do Trabalho, Santa Maria-RS